Análise das microdeformações geradas ao redor de implantes de hexágono externo sob a aplicação de cargas verticais em pilares microunit retos e angulados - Louzada, Frederico Freire [UNESP] (2014)
The aim of this study was to evaluate in vitro, by means of strain gauge analysis, the stress distribution around implants with external hexagon connection facing different tilt situations. Two blocks of polyurethane were used, in first block the 3 implants were installed parallel to each other and inclined at 17 degrees, and the second block 3 implants were installed parallel to each other and perpendicular to the surface, then their abutments were connected to correct angulation, being screwed with a torque of 20 N.cm. Plastic hoods were installed and united to 10 acrylic resin structures for each group. In the block area, four strain gauges were glued tangent to each implant. Vertical static loads of 30 kg with 10 second intervals over three retaining screws of the structure. The data obtained by the strain under three replicates were subjected to ANOVA. Average of 294.32 ± 284.44 με were recorded around implants positioned axially and average of 300.74 ± 238.85 με for the group with tilted implants. There was no significant difference between the group with implants straight and the group with tilted implants, no significant difference in microstrain between different points of load application. As conclusion, we observed the use of tilted implants in 17 degrees presents results of microstrain similar to axial implants